2021
DOI: 10.1002/ppul.25688
|View full text |Cite
|
Sign up to set email alerts
|

Cord‐blood respiratory syncytial virus antibodies and respiratory health in first 5 years of life

Abstract: Objective: To determine the potential longer-term effects of maternal antenatal respiratory syncytial virus (RSV) vaccination, we examined the association between cord-blood RSV-neutralizing antibodies (RSV-NA) and RSV infections in the first 2 years of life, RSV-NA at 3 years, and respiratory health to age 5 years.Methods: Two community-based Australian birth cohorts were combined. For children with at least one atopic parent, paired serum RSV-NA levels were compared in cord blood and at age 3 years. Weekly n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
(125 reference statements)
0
2
0
Order By: Relevance
“…Such vaccine candidate might be an active vaccine given shortly after birth or a maternal vaccine given during late pregnancy anticipating placental transfer of anti-RSV maternal IgG antibodies to the foetus [ 45 – 47 ]. A recent study showed no protective effect of increased level of cord-blood RSV-neutralizing antibodies against acute RSV infection during the first 6 months of life, although protection was evident at age 12–24 months [ 48 ]. A randomised controlled phase III clinical trial with RSV fusion protein nanoparticle vaccine, which included 4579 pregnant women, showed no significant protection against the prespecified endpoint for the efficacy of RSV-associated, medically significant lower respiratory tract infection up to age 90 days after vaccination (vaccine efficacy was 39.4%) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such vaccine candidate might be an active vaccine given shortly after birth or a maternal vaccine given during late pregnancy anticipating placental transfer of anti-RSV maternal IgG antibodies to the foetus [ 45 – 47 ]. A recent study showed no protective effect of increased level of cord-blood RSV-neutralizing antibodies against acute RSV infection during the first 6 months of life, although protection was evident at age 12–24 months [ 48 ]. A randomised controlled phase III clinical trial with RSV fusion protein nanoparticle vaccine, which included 4579 pregnant women, showed no significant protection against the prespecified endpoint for the efficacy of RSV-associated, medically significant lower respiratory tract infection up to age 90 days after vaccination (vaccine efficacy was 39.4%) [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, most cases of RSV occur in the first months of life, when the levels of maternal NA may be considered substantially higher. 82 , 149 , 150 …”
Section: Maternal Vaccinesmentioning
confidence: 99%